Protein O-Mannosyltransferases Associate with the Translocon to Modify Translocating Polypeptide Chains - Loibl, Martin; Hutzler, Johannes; Strahl, Sabine (The journal of biological chemistry, 2014)
O-Mannosylation and N-glycosylation are essential protein modifications that are initiated in the endoplasmic reticulum (ER). Protein translocation across the ER membrane and N-glycosylation are highly coordinated processes that take place at the translocon-oligosaccharyltransferase (OST) complex. In analogy, it was assumed that protein O-mannosyltransferases (PMTs) also act at the translocon, however, in recent years it turned out that prolonged ER residence allows O-mannosylation of un-/misfolded proteins or slow folding intermediates by Pmt1-Pmt2 complexes. Here, we reinvestigate protein O-mannosylation in the context of protein translocation. We demonstrate the association of Pmt1-Pmt2 with the OST, the trimeric Sec61, and the tetrameric Sec63 complex in vivo by co-immunoprecipitation. The coordinated interplay between PMTs and OST in vivo is further shown by a comprehensive mass spectrometry-based analysis of N-glycosylation site occupancy in pmtΔ mutants. In addition, we established a microsomal translation/translocation/O-mannosylation system. Using the serine/threonine-rich cell wall protein Ccw5 as a model, we show that PMTs efficiently mannosylate proteins during their translocation into microsomes. This in vitro system will help to unravel mechanistic differences between co- and post-translocational O-mannosylation.